In Situ Environmental Transmission Electron Microscopy Investigation on LiH Formation Prompted by LiF - Yu, Xinyang; Ruan, Digen; Ma, Yuan; Zheng, Xuzhi; Hua, Ze; Shao, Ruiwen; Wang, Dazhuang; Kang, Zhuo; Ren, Xiaodi; Qiao, Lijie; He, Yang (Nano letters, 2025)
Lithium hydride is a common but unfavorable component that leads to “dead Li” formation in lithium batteries. Since the hydrogen sources in the batteries are diverse and hardly evitable, unraveling the key factors promoting LiH formation is fundamentally crucial in improving lithium batteries’ cycling stability. Herein, by using in situ environmental transmission electron microscope, we revealed a critical role of lithium fluoride in the LiH formation during the electrochemical deposition of Li in a hydrogen environment, presumably by facilitating the kinetic process of hydrogen dissociation and the LiH nucleation. Ex situ coin-cell studies and DFT calculations corroborate this finding, further suggesting that the commonly used fluorine-rich electrolytes could promote LiH formation. Additionally, the LiH lattices in the dendrites are distorted and likely nonstoichiometric with face-centered cubic structured domains of Li metal. These fundamental insights on the LiH formation may pave the way for enhancing the cycle stability of lithium batteries.